Penerapan Model Pembelajaran Kooperatif Picture To Picture Untuk Meningkatkan Keterampilan Proses Siswa Pada Pembelajaran IPA - Sumarno Sumarno; Sri Handayani; Sri Sumiyati; Triyoto Triyoto; Edi Prayitno (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2019)
This research was conducted in Kutoharjo Elementary School 2, Rembang Regency. The subjects of this study were 28 students in class V, 11 girls and 17 boys. This research begins with the problem of low student process skills in science subjects with water cycle material. Research in the form of Classroom Action Research (CAR) with three cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. Cycle I process skill scores reached 65 with enough categories. Cycle II score of process skills reached 72. Cycle III score of process skills reached 84 with good categories. The increase in process skill scores in the three learning cycles provides evidence that the Picture to Picture Cooperative Learning Model has succeeded in improving students' process skills in science learning with water cycle material.